Mastitis dengan Depresi Postpartum: Literature Review - Ahmaniyah, Ahmaniyah; Indriyani, Ratna; Hidayati, Niken Wahyu; Aulia, Aulia; Satriawati, Arisda Candra (Wiraraja Medika : Jurnal Kesehatan, 2023)
Mastitis is an inflammatory condition that occurs in breastfeeding mothers in the first month postpartum. The incidence of mastitis is around 9-20% which is caused by a lack of frequency of breastfeeding, errors in breastfeeding and pressure on the breast tissue. In this study, we examined the relationship between mastitis and postpartum depression. reviewed from Google Scholar database and other related websites. With the keywords "mastitis, depression, postpartum". A total of 3 out of 3,140 were then selected according to the theme and similarities were searched for from each journal found. Publication range from 2019 to October 2023. obtained from a population of 1,555 people who experienced mastitis, 147 with significant results of 68% that those who experienced mastitis would harm themselves and desire suicide and mothers over 35 years of age would be more at risk of developing depression Mothers who breastfed were 74.67 ± 4.35; the average EPDS score was 5.73 ± 4.34. And mothers suffering from lactational mastitis had higher EPDS scores at 34-38 weeks of gestation and experienced an increase in EPDS scores. at 6 weeks postpartum The occurrence of physical difficulties or health problems during breastfeeding has been associated with a greater risk of developing mental symptoms of health problems in the postpartum period. In particular, several prospective studies have shown that there is an association between the presence of physical health problems and the first 3 months (or more) after giving birth and the emergence of depressive symptoms in women at the age of 6 to 12 months postpartum